The Polycomb Protein Bmi1 Plays a Crucial Role in the Prevention of 1, 25(OH)2D Deficiency‐Induced Bone Loss. (17th December 2019) - Sun, Haijian; Qiao, Wanxin; Cui, Min; Yang, Cuicui; Wang, Rong; Goltzman, David; Jin, Jianliang; Miao, Dengshun
ABSTRACT: We analyzed the skeletal phenotypes of heterozygous null Cyp27b1 ( Cyp27b1 +/− ) mice and their wild‐type (WT) littermates to determine whether haploinsufficiency of Cyp27b1 accelerated bone loss, and to examine potential mechanisms of such loss. We found that serum 1, 25‐dihydroxyvitamin D [1, 25(OH)2 D] levels were significantly decreased in aging C yp27b1 +/− mice, which displayed an osteoporotic phenotype. This was accompanied by a reduction of expression of the B lymphoma Moloney murine leukemia virus (Mo‐MLV) insertion region 1 (Bmi1) at both gene and protein levels. Using chromatin immunoprecipitation (ChIP)‐PCR, electrophoretic mobility shift assay (EMSA) and a luciferase reporter assay, we then showed that 1, 25(OH)2 D3 upregulated Bmi1 expression at a transcriptional level via the vitamin D receptor (VDR). To determine whether Bmi1 overexpression in mesenchymal stem cells (MSCs) could correct bone loss induced by 1, 25(OH)2 D deficiency, we overexpressed Bmi1 in MSCs using Prx1 ‐driven Bmi1 transgenic mice ( Bmi1 Tg ) mice. We then compared the bone phenotypes of Bmi1 Tg mice on a Cyp27b1 +/− background, with those of Cyp27b1 +/− mice and with those of WT mice, all at 8 months of age. We found that overexpression of Bmi1 in MSCs corrected the bone phenotype of C yp27b1 +/− mice by increasing osteoblastic bone formation, reducing osteoclastic bone resorption, increasing bone volume, and increasing bone mineral density. Bmi1 overexpression in MSCs also corrected 1, 25(OH)2 D deficiency‐induced oxidative stress and DNA damage, and cellular senescence of C yp27b1 +/− mice by reducing levels of reactive oxygen species (ROS), elevating serum total superoxide dismutase levels, reducing the percentage of γH2 A.X, p16, IL‐1β, and TNF‐α–positive cells and decreasing γH2A.X, p16, p19, p53, p21, IL‐1β, and IL‐6 expression levels. Furthermore, 1, 25(OH)2 D stimulated the osteogenic differentiation of MSCs, both ex vivo and in vitro, from WT mice but not from Bmi1 −/− mice and 1, 25(OH)2 D administration in vivo increased osteoblastic bone formation in WT, but not in Bmi1 −/− mice. Our results indicate that Bmi1, a key downstream target of 1, 25(OH)2 D, plays a crucial role in preventing bone loss induced by 1, 25(OH)2 D deficiency. © 2019 American Society for Bone and Mineral Research.